2008
DOI: 10.1007/s11356-008-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

A decision framework for possible remediation of contaminated sediments in the River Kymijoki, Finland

Abstract: The studies form the basis of a risk management strategy and a plan for possible remediation of contaminated sediments currently under consideration in the Southeast Finland Regional Environment Centre. It is recommended that a detailed restoration plan for the most seriously contaminated areas should be undertaken. Based on current knowledge, the restoration of the whole river is not feasible, considering the current risk caused by the contaminated sediment in the river and the costs of an extensive restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…In the present study, the most abundant PCDD/F-congeners were OCDF and 1,2,3,4,6,7,8-HpCDF, the latter being impurity of the previous manufacture of wood-preservative (Ky-5), and the most common congener in R. Kymijoki sediments also in the studies of Salo et al (2008) and Verta et al (2009).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the present study, the most abundant PCDD/F-congeners were OCDF and 1,2,3,4,6,7,8-HpCDF, the latter being impurity of the previous manufacture of wood-preservative (Ky-5), and the most common congener in R. Kymijoki sediments also in the studies of Salo et al (2008) and Verta et al (2009).…”
Section: Discussionsupporting
confidence: 54%
“…Pollution history (PCDD/Fs, PCBs, Hg) and gradients in the R. Kymijoki are described by Salo et al (2008) and Verta et al (2009). Surface sediment samples were collected in two replicates from six sites, Kuusaansaari (sample codes 1A and 1B), Keltti (2A, 2B), Lopotti (3A, 3B), Koskenalusjärvi (4A, 4B), Ahvionkoski (5A, 5B) and Kyminlinna (6A, 6B) along a longitudinal contamination gradient in R. Kymijoki, and from one site in R. Urpalanjoki (7A, 7B) in July 2012 (Fig.…”
Section: The Study Sedimentsmentioning
confidence: 99%
“…Verta et al (2009) reported that more than 30 tons of mercury was emitted to the River Kymijoki between the 1940'ies and 1971, which has been shown in many studies from the Gulf of Finland (Kokko, Turunen 1988;Vallius 2012). The concentrations of Hg in the sediments of the contaminated north-eastern part of the Gulf of Finland are very high.…”
Section: Spatial Distribution Of the Studied Elementsmentioning
confidence: 93%
“…Verta et al (2009) reported that more than 30 tons of mercury were emitted into the River Kymijoki between the 1940s and 1971.…”
Section: Horizontal Distributionmentioning
confidence: 99%